Analysis Customer Interest in Purchasing Digital Accounts Through X - Gonzalez, Pedro; Gunawan, Diah Setyorini; Gunawan, Ratna Setyawati (Lingka Ekonomika, 2025)
This study examines the influence of price, service quality, ease of transaction, and brand loyalty on customer interest in purchasing digital accounts on social media X. Using a quantitative approach with primary data from questionnaires completed by students of the Faculty of Economics and Business, Universitas Jenderal Soedirman (class of 2018–2022, aged 18–24), the study applies simple random sampling and multiple linear regression analysis. The results indicate that price and ease of transaction negatively affect customer interest, while service quality and brand loyalty have positive effects. It implies that affordable prices must be supported by good service, smooth transactions, and diverse digital products to enhance customer interest.